Transformation of Traditional Marketing to E-Marketing: A Theoretical Review of Digital Technology Utilization Impact Against Business Marketing Competitiveness - Paramastri, Dea Kriseta (Riwayat: Educational Journal of History and Humanities, 2024)
This research is a literature review aimed at describing the impact of the transformation from traditional marketing to E-Marketing, focusing on the use of digital technology on business marketing competitiveness. Through the literature review method, this research collected and analyzed various literature sources from scientific journals, books, articles, and research reports related to the topic. The literature review results show that digital technology has influenced how businesses interact with consumers and how companies manage marketing information. Social media, websites, and mobile applications have enabled companies to reach consumers more efficiently and effectively. Analytical technology and big data have also provided valuable insights into consumer behaviour, allowing companies to develop targeted and personalized marketing strategies. However, this research also reveals that the transformation to E-Marketing brings challenges. Competition in the digital world is increasingly fierce, forcing companies to innovate continuously to differentiate themselves from competitors and attract consumer interest. Additionally, privacy and data security issues have become critical, and companies must take proactive steps to protect consumer data and build strong trust.